2012
DOI: 10.3727/096368912x652959
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Can Abrogate Chemical-Induced Liver Fibrosis and Facilitate Recovery of Liver Function

Abstract: Adipose-derived stem cells (ADSCs) are easy to harvest and have the ability for self-renewal and to differentiate into various cell types, including those of the hepatic lineage. Studies on the use of ADSCs for liver transplantation are, however, limited. The objective of this study was to investigate the feasibility of using human ADSCs and to better understand their mechanism of action for the repair of liver damage in a thioacetamide (TAA)-induced model of chronic liver damage in the rat. To induce liver da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 25 publications
7
90
0
3
Order By: Relevance
“…However, this study is unable to confirm differentiation at the functional level. In contrast, human ASCs induced toward the hepatocyte lineage and directly injected into models of liver fibrosis are found to secrete albumin and -fetoprotein, decrease fibrosis and inflammation and improve liver function [256]. Similarly, induced human ASCs transplanted into CCl 4 -injured livers in nude mice not only increase their production of albumin protein but also restore liver functions such as ammonia and purine metabolism and decrease liver injury markers, such as alanine aminotransferase and aspartate aminotransferase activity [159].…”
Section: In Vivo Endoderm Regenerationmentioning
confidence: 99%
“…However, this study is unable to confirm differentiation at the functional level. In contrast, human ASCs induced toward the hepatocyte lineage and directly injected into models of liver fibrosis are found to secrete albumin and -fetoprotein, decrease fibrosis and inflammation and improve liver function [256]. Similarly, induced human ASCs transplanted into CCl 4 -injured livers in nude mice not only increase their production of albumin protein but also restore liver functions such as ammonia and purine metabolism and decrease liver injury markers, such as alanine aminotransferase and aspartate aminotransferase activity [159].…”
Section: In Vivo Endoderm Regenerationmentioning
confidence: 99%
“…To date, ADSCs have become excellent candidates for research and clinical applications. Many studies have shown that ADSC transplantation efficiently improved almost all symptoms of certain diseases, such as liver fibrosis (Harn et al, 2012), nerve defects (Gu et al, 2012;Liu et al, 2011;Santiago et al, 2009), ischemia (Mazo et al, 2012;Rigol et al, 2010), skeletal muscle injury (Pecanha et al, 2012), passive chronic immune thrombocytopenia (Xiao et al, 2012), and myocardial infarction (Yang et al, 2012) in animals, and systemic sclerosis in humans (Riordan et al, 2009;Scuderi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, ADSCs could degrade collagen fiber by increasing the expression of matrix metalloproteinase-9. Therefore, ADSCs could abrogate chemical-induced liver fibrosis (32). Moreover, after ADSC or CM-ADSCs injected to scars, Zhang Q confirmed that the regular collagen architecture was recovered and that the expression of αSMA and collagen type Ι were also decreased by histomorphometric and real-time quantitative polymerase chain reaction analysis (33).…”
Section: Discussionmentioning
confidence: 68%